Species suitability for small indigenous species (SIS) of fish farming in carp polyculture ponds under drought prone area - Harun-Ur-Rashid, Md.; Hossain, Md. Akhtar; Mondol, Md. Mostafizur Rahman; Nabi, S.M. Nurun; Sikendar, Md. Abu; Hossain, Md. Anwar (Journal of Fisheries, 2021)
Reduced culture period with lack of guidelines in selecting appropriate species are major constraints for promotion of small indigenous species (SIS) based carp polyculture in ponds under drought prone area. In order to address this issue, an experiment was conducted to determine the suitable species for farming of SIS fishes in carp polyculture ponds in Rajshahi district, Bangladesh. Three different species of SIS fishes were tested under three treatments (T1, Heteropneustes fossilis; T2, Clarias batrachus; T3, Mystus cavasius). Carp species were Hypophthalmichthys molitrix, Gibelion catla and Labeo rohita. Stocking density of SIS fishes (37050 individuals ha–1) and carps (H. molitrix, 500; G. catla, 250 and L. rohita 250 individuals ha–1) were same for all the treatments. Fishes were fed 35% protein containing supplementary feed twice a day at the rate of 6% of biomass. Common water quality parameters were monitored monthly and found within the suitable range for fish culture. Treatment T2 was significantly higher than others in terms of fish yield and cost benefit ratio. Further research is also recommended to optimize the stocking density of C. batrachus based carp polyculture.